SUSTAINABLE BUSINESS MODELS RESEARCH: A BIBLIOMETRIC ANALYSIS - Xhorxhina VANGJEL; Olimpia BAN (Annals of the University of Oradea: Economic Science)
A variety of studies are being developed to investigate sustainable business models. This research is part of a wider one and aims at the theoretical deepening of the existing paradigms in the literature. The realization of the bibliometric analysis in the field of sustainable business models was mainly influenced by the extent of this type of business models. The data in this study were collected through the use of bibliometric tools, identifying and then analyzing the most influential and cited publications from the Scopus and Google Scholar Metrics platforms for the same time periods. The keyword phrase was searched in the databases as a first step that initiates the continuation of this analysis. This action helps to obtain valuable data for the purpose of this study. The inspiration of the topic is guided by two objectives formulated in the form of research questions: In empirical studies how is the sustainability of a business evaluated? What are the dimensions that lead to the sustainability of business models, the focus on which can reveal previously unexplored directions? We emphasize that from the total of 20 studies selected for the bibliometric analysis, 14 of them are original articles and 6 are review analyses. Some criteria or exponents of research units serve to conclude the findings and conclusions of the bibliometric analysis. The construction of a comprehensive visual analysis represented in the following figures and graphs corresponds precisely to the results achieved by this research. Then, in this framework we integrate the framework findings-results for the search for sustainable business models. The findings of this study indicate that the trend of the production of academic studies in the field of sustainability of business models is relatively positive. We aim to identify the state of research and the possibility of completing it with a current documentary or empirical analysis useful for the two countries, Romania and Albania. On sustainable business models, in the future we propose to do a case study on the evolution of the production activity system from eco-design and the effective implementation of eco-innovative practices in these two countries, in order to capitalize on the results obtained from the bibliometric analysis.